Open-label riluzole in fragile X syndrome - Erickson, Craig A.; Weng, Ning; Weiler, Ivan Jeanne; Greenough, William T.; Stigler, Kimberly A.; Wink, Logan K.; McDougle, Christopher J. (Brain research, 2011)
Objective. Glutamatergic dysregulation is implicated in the pathophysiology of fragile X syndrome (FXS). Riluzole is hypothesized to have an inhibitory effect on glutamate release, block excitotoxic effects of glutamate, and potentiate postsynaptic GABA(A) receptor function. Extracellular signal-related kinase (ERK) activation is known to be delayed in humans with FXS and knockout animal models of FXS. Correction of delayed ERK activation is a potential biomarker of treatment response in FXS. We conducted a six-week open-label prospective pilot study of riluzole (100 mg/day) in six adults with FXS. Methods. Riluzole was started at 50 mg every evening and then increased to 50 mg twice daily at week 2. The dose was kept constant for the final 4 weeks of the trial. Clinical response was determined by a score of 1 “very much improved” or 2 “much improved” on the Clinical Global Impressions Improvement (CGI-I) scale and a ≥ 25% improvement on the Children's Yale-Brown Obsessive Compulsive Scale modified for Pervasive Developmental Disorders. The primary target of treatment in this study was repetitive, compulsive behavior that commonly occurs in persons with FXS. The study incorporated an ERK activation biomarker assay. Potential adverse effects were assessed in a systematic manner at all clinic visits and by phone between visits. Results. Riluzole treatment was associated with clinical response in 1 of 6 subjects (17%). Among a number of secondary outcome measures employed, significant improvement was only noted on the ADHD Rating Scale-IV (became non-significant when corrected for multiple comparisons). Riluzole use was associated with significant correction in ERK activation time in all subjects (mean change from 3.82 ± 0.27 (baseline) to 2.99 ± 0.26 (endpoint) minutes; p = 0.007). Riluzole was well tolerated; mean increases in liver function tests occurred but drug discontinuation was not required. Conclusion. Overall, riluzole use was not associated with significant clinical improvement despite uniform correction of peripheral ERK activation. Future directions of study include testing of riluzole in animal models of FXS and assessment of psychotropic monotherapy on ERK activation. ► Riluzole use was associated in clinical improvement in only 1 of 6 subjects. ► Despite limited clinical change, the ERK activation (a biomarker of treatment response) improved in all cases. ► Riluzole use warrants future systematic study to better predict potential treatment response.